Comparison of IgG and Neutralizing Antibody Response After Pfizer BioNTech COVID-19 Vaccine Among Iraqi Individuals - Najat Saeed Hussein; Izzat Abdulsatar Al-Rayahi; Salwa S. Muhsin; Redhwan Abdul Kareem Alameer (Journal of Techniques)
SARS-C0V-2 has quickly caused a pandemic. The distribution of vaccines is presently underway in an effort to stop the viral transmission and stop fatalities, several vaccinations have been created to decrease COVID virus disease, in 2019, the development of vaccine-induced population immunity is an important global strategy. Review of the anti-spike protein receptor-binding domain (S-RBD) a person's level of immune response to antibody strategy can be used to assess SARS-CoV-2 viral infection in 2019.  Their efficacy, safety, and immunogenicity in various population are not thoroughly understood. The objective of this study was to evaluate the vaccinations adverse effects as well as determine the immunogenicity of the messenger ribonucleic acid (mRNA) BNT162b2 vaccines through the production of IgG and neutralizing antibodies against the protein s subunit. A total of 41 vaccinated individuals with Pfizer-BioNTech COVID-19 vaccine, as well as (10) non vaccinated were included in the study.   Measurements of Neutralizing antibody (Nab) levels and CoV-IgG levels were tested by fluorescence Immunochromatographic assay. IgG and Nab levels showed a significant difference between its level in the sera of vaccinated and controls (p<0.05). This means the majority of immunization recipients between the ages of 18 -50 years can develop an immunological response to the SARS-Cov-2 vaccine.